A NEED ANALYSIS OF READING MEDIA TO SUPPORT READING ENGAGEMENT AND GENDER EQUALITY IN EARLY CHILDHOOD EDUCATION - Ni Putu Dwi Yanti; Luh Gd Rahayu Budiarta; Ni Luh Putu Era Adnyayanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Reading engagement and gender equality are important aspects of early childhood education because both contribute to children’s literacy development and social awareness from an early age. However, reading materials used in early childhood classrooms generally still focus on basic literacy skills and rarely integrate gender equality values. This study aimed to identify teachers’ and students’ needs for reading materials that support reading engagement while promoting gender equality in early childhood education. This study employed a qualitative descriptive design using a needs analysis approach. Data were collected through classroom observations and interviews with a kindergarten teacher in TK B class at TK Danend Kiddy School Singaraja. The findings indicate that students’ reading engagement was low and inconsistent when using conventional, small-sized reading materials, which limited students’ attention and participation during reading activities. In addition, the teacher expressed the need for large-sized, engaging, and developmentally appropriate reading materials that are able to introduce gender equality values in a simple and meaningful way. These findings suggest that the development of reading materials, such as Big Books, is necessary to enhance reading engagement and foster awareness of gender equality among early childhood learners. ABSTRAK Keterlibatan membaca dan kesetaraan gender merupakan aspek penting dalam pendidikan anak usia dini karena keduanya berkontribusi terhadap perkembangan literasi dan kesadaran sosial anak sejak usia dini. Namun, bahan bacaan yang digunakan di kelas pendidikan anak usia dini umumnya masih berfokus pada keterampilan literasi dasar dan jarang mengintegrasikan nilai kesetaraan gender. Penelitian ini bertujuan untuk mengidentifikasi kebutuhan guru dan siswa terhadap bahan bacaan yang dapat mendukung keterlibatan membaca sekaligus mempromosikan kesetaraan gender dalam pendidikan anak usia dini. Penelitian ini menggunakan desain deskriptif kualitatif dengan pendekatan analisis kebutuhan. Data dikumpulkan melalui observasi kelas dan wawancara dengan seorang guru taman kanak-kanak pada kelas TK B di TK Danend Kiddy School Singaraja. Hasil penelitian menunjukkan bahwa keterlibatan membaca siswa masih rendah dan tidak konsisten ketika menggunakan bahan bacaan konvensional berukuran kecil, sehingga membatasi perhatian dan partisipasi siswa selama kegiatan membaca. Selain itu, guru menyampaikan kebutuhan akan bahan bacaan berukuran besar, menarik, sesuai dengan tahap perkembangan anak, serta mampu mengenalkan nilai kesetaraan gender secara sederhana dan bermakna. Temuan ini menunjukkan bahwa pengembangan bahan bacaan seperti Big Book diperlukan untuk meningkatkan keterlibatan membaca dan menumbuhkan kesadaran kesetaraan gender pada anak usia dini.